RASKES : a random access symmetric-key encryption system - Liu, Pengbo. (2008)
In this thesis, a new encryption system framework is proposed. The level of security achievable is similar to that of Shannon’s unbreakable one-time pad. This new approach also overcomes some known limitations of current encryption approaches. The process, for the purpose of discussion, is called the Random Access Symmetric-key Encryption System.